On the role of initial velocities in pair dispersion in a microfluidic chaotic flow - Eldad Afik (Nature Portfolio, 2017)
Elastic turbulence, a random-in-time flow, can drive efficient mixing in microfluidics. Using a 3D particle tracking method, the authors show that the smoothness assumption breaks at scales far smaller than believed and the ballistic pair dispersion holds over much longer distances than expected.